2020
DOI: 10.1155/2020/6940625
|View full text |Cite
|
Sign up to set email alerts
|

Silicone Oil Emulsification after Vitrectomy for Rhegmatogenous Retinal Detachment

Abstract: is properly cited.Purpose. To investigate the characteristics of silicone oil (SO) emulsification after vitrectomy for rhegmatogenous retinal detachment and their possible correlations with clinical factors. Methods. e first 2 mL of washing out fluid after SO removal was collected, and used for the measurement of the size and number of SO droplets using a Multisizer ® 3 Coulter counter (Beckman Coulter, USA). e correlations between SO droplets and clinical factors were analyzed. Results. A total of 38 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 18 publications
(19 reference statements)
1
14
0
1
Order By: Relevance
“…Interestingly, using these devices, the majority of droplets have been found to be below 2 μm in size, which is too small to be observed clinically via gonioscopy or slit‐lamp biomicroscopy. Recent clinical studies also obtained similar findings (Yu et al 2020a; Yu et al 2020b). This information may account for some otherwise clinically unexplained complications related to SO, namely secondary glaucoma without observable emulsification, and provide future research directions.…”
Section: Properties Of Silicone Oil Its Indications Complications and Emulsificationsupporting
confidence: 71%
“…Interestingly, using these devices, the majority of droplets have been found to be below 2 μm in size, which is too small to be observed clinically via gonioscopy or slit‐lamp biomicroscopy. Recent clinical studies also obtained similar findings (Yu et al 2020a; Yu et al 2020b). This information may account for some otherwise clinically unexplained complications related to SO, namely secondary glaucoma without observable emulsification, and provide future research directions.…”
Section: Properties Of Silicone Oil Its Indications Complications and Emulsificationsupporting
confidence: 71%
“…It has been reported that the extent of silicone oil emulsification was more severe in younger patients. 37 Therefore, silicone oil is recommended to be removed once the vitreoretinal disorders are stationary, especially in young patients. In our study, the silicone oil was removed in patients in groups 2 and 3, who were younger than those in groups 1 and 4.…”
Section: One Challenge Of the Postvitrectomy Cataractmentioning
confidence: 99%
“…We found that the grade of SO emulsi cation was correlated with younger age and male gender. Previous studies [4,10] also reported a correlation between SO emulsi cation and age. Aqueous proteins and eye movement, which facilitate SO emulsi cation and are greater in younger eyes, might be contributing factors [11].…”
Section: Discussionmentioning
confidence: 64%